EVALUATING THE EFFECT OF POULTRY MANURE ON THE PERFORMANCE OF WHEAT UNDER THE AGROECOLOGICAL ZONE OF MANSEHRA, KHYBER PAKHTUNKHWA, PAKISTAN - ULLAH , A; ALI , H; ALI , F; ALI, H; KHAN , BJ; SAEED , F; IQBAL , A; HASSAN , MU (Biological and Clinical Sciences Research Journal, 2024)
The conducted research aims at the effects of poultry manure on wheat (Triticum aestivum) growth, yield, and quality. Poultry manure is widely used as an organic fertilizer due to its high concentration of nutrients, particularly nitrogen, phosphorous, and potassium. This experiment was carried out in the Agricultural Research Farm, Department of Agriculture, Hazara University Mansehra in Khyber Pakhtunkhwa, Pakistan, during the summer of 2022–2023. Three replications of a randomized complete block design (RCBD) were used in the experiment. Four treatments of poultry manure application (control, 204g/3.48 m2, 340g/3.48 m2, and 680g/3.48 m2) were tested for wheat. Many morphological and yield-related characteristic data were collected, including plant height, spike length, number of spikelet’s per spike, thousand-grain weight, grain yields (kg/ha-1), and biological yields (kg/ha-1) under agro-climatic conditions of Mansehra, which means that the wheat on different Poultry manure doses shows improvement in plant height, spike length, spikelet’s per spike and thousand-grain weight. The findings showed that the appropriate use of poultry manure can significantly enhance wheat productivity and improve soil health. Based on these results it is recommended that wheat give the best yield in 680 grams per 3.43 m2 (100% of nutrient requirement) manure application.